Factors associated with the completion of antenatal care in Indonesia: A cross-sectional data analysis based on the 2018 Indonesian Basic Health Survey - Haerawati Idris; Indah Sari (Belitung Nursing Journal, 2023)
Background: The global incidence of maternal mortality remains high, including in Indonesia, and the utilization of antenatal care services can help reduce these rates. Despite numerous studies examining factors affecting antenatal care utilization, there has been limited focus on identifying factors related to the completion of these services. Objective: This study aimed to analyze factors associated with the completion of antenatal care in Indonesia. Methods: The study used a cross-sectional analysis of secondary data from the Basic Health Research conducted by the Indonesian Ministry of Health in March 2018. The sample consisted of 65,929 pregnant women aged 15 to 49. Descriptive statistics, chi-square tests, and multiple logistic regression were used for data analysis. Results: The majority of respondents (75.2%) completed antenatal care. Factors significantly correlated with antenatal care completion were education level, occupation status, health insurance ownership, place of antenatal care services, travel time to health facilities, area of residence, history of pregnancy, parity, desired pregnancy, and pregnancy complications (p <0.05). The multiple logistic regression test showed that education level was the most dominant factor associated with antenatal care completion (p <0.001, OR = 2.023, 95% CI = 1.839-2.225). Conclusion: Completion of antenatal care is influenced by various factors, including education, job status, health insurance ownership, antenatal care services’ location, travel time to health facilities, residence area, previous pregnancy history, number of children, desired pregnancy, and pregnancy complications. However, education is crucial in determining a mother’s understanding and approach toward using these services. The Indonesian government should enhance public education and awareness initiatives to increase utilization. Healthcare professionals, particularly nurses and midwives, play a vital role in educating pregnant women about the significance of utilizing prenatal care services consistently and facilitating their access to these services efficiently.